Obstruction of Justice by Lawyer Fredrich Yunadi in the Corruption Case of the E-KTP (Electronic Identity Card) Procurement Project Involving Former People's Representative Council Chairman Setya Novanto - Daniel Halomoan; Figo Edsel Hidayat; Jaya Pahlevi; Rezki Tama A.P; Rofik Cahya Arta; William Rando Bayakta (Universitas Pelita Harapan, 2023)
Many lawyers have encountered cases of legal obstruction, which raises concerns since advocates are a respected profession within law enforcement. This paper aims to: (1) provide examples of cases and explain the modus operandi and working system in the case of Fredrich Yunadi's legal obstruction; (2) examine how legal obstacles have become phenomena within the legal profession; (3) offer sociological and psychological perspectives from criminologists; and (4) investigate the implementation and process of punishment for the perpetrators. This research falls under the category of normative research, as the author examines library and secondary materials. The study reviews positive law and legal principles. Primary legal materials, secondary legal materials, and tertiary legal materials serve as the data sources. The data collection method employed is library research or documentary studies. Based on the research findings, two main conclusions can be drawn. First, law enforcement actions in Indonesia have not effectively prevented advocates from being prosecuted for corruption, as not all legal subjects comply with relevant legal norms. This is influenced by three components of law enforcement: legal substance, law enforcement, and legal culture. Second, the connection between law enforcement and lawyers accused of obstructing justice with advocates' right to immunity is related to the fact that the position of advocates is vulnerable to intersect with obstruction of justice when advocates define their right to immunity without considering the limitations stipulated in laws and regulations. This highlights the importance of advocating a code of ethics for advocates.